Tango and Paella. Teachers from Buenos Aires and Valencia Curating Exhibitions with an educational focus - Huerta, Ricard (2014)
This paper proposes a new approach to managing and curating exhibitions, analyzing two exhibition projects with a strong participatory emphasis, focusing on the social aspect of these proposals. In both cases, the curators have prepared ajoint educational discourse. The Valencian «Disease’s Calligraphy» and the Buenos Aires «When I say School» consider the visitors as actors, performers and builders of meanings. The exhibitions create conditions of appropriation of heritage and offer quality experiences for different users developing their perspectives, knowledge, narrative and emotions.